Potensi Hutan Rakyat Sebagai Penghasil Pangan di Desa Paku Kabupaten Polman, Sulawesi Barat - Daud Irundu; Fatmawati D (Fakultas Kehutanan, Universitas Hasanuddin, 2019)
Food security is one of the efforts to create people's prosperity, related to this, the role of various sectors is needed to contribute in national food security programs. Every region has a community forest that produces food to meet the needs of its people. So far, information regarding forest food in West Sulawesi is still very minimal. This study provides information about the potential of community forests as food producers in Paku Village, Binuang District, Polman Regency. The time of the study was carried out from March to December 2018. This study used survey and interview methods for 12 respondents in locations that randomly plotted 20 x 20 meters. Data analysis using descriptive quantitative. The results of this study indicate that the potential of community forests in Paku Village in supporting good food needs, from community forests is able to produce 46.01% of food commodities consisting of 12 types of food based on the form of agroforestry. Some dominant types of food are sugar palm (Arenga pinnata), Cocoa (Theobroma cacao), Mango (Mangifera indica).